Burden of non-communicable diseases in sub-Saharan Africa, 1990–2017: results from the Global Burden of Disease Study 2017. Issue 10 (October 2019) - Gouda, Hebe N; Charlson, Fiona; Sorsdahl, Katherine; Ahmadzada, Sanam; Ferrari, Alize J; Erskine, Holly; Leung, Janni; Santamauro, Damian; Lund, Crick; Aminde, Leopold Ndemnge; Mayosi, Bongani M; Kengne, Andre Pascal; et al.
Summary: Background: Although the burden of disease in sub-Saharan Africa continues to be dominated by infectious diseases, countries in this region are undergoing a demographic transition leading to increasing prevalence of non-communicable diseases (NCDs). To inform health system responses to these changing patterns of disease, we aimed to assess changes in the burden of NCDs in sub-Saharan Africa from 1990 to 2017. Methods: We used data from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2017 to analyse the burden of NCDs in sub-Saharan Africa in terms of disability-adjusted life-years (DALYs)—with crude counts as well as all-age and age-standardised rates per 100 000 population—with 95% uncertainty intervals (UIs). We examined changes in burden between 1990 and 2017, and differences across age, sex, and regions. We also compared the observed NCD burden across countries with the expected values based on a country's Socio-demographic Index. Findings: All-age total DALYs due to NCDs increased by 67·0% between 1990 (90·6 million [95% UI 81·0–101·9]) and 2017 (151·3 million [133·4–171·8]), reflecting an increase in the proportion of total DALYs attributable to NCDs (from 18·6% [95% UI 17·1–20·4] to 29·8% [27·6–32·0] of the total burden). Although most of this increase can be explained by population growth and ageing, the age-standardised DALY rate (per 100 000 population) due to NCDs in 2017 (21 757·7 DALYs [95% UI 19 377·1–24 380·7]) was almost equivalent to that of communicable, maternal, neonatal, and nutritional diseases (26 491·6 DALYs [25 165·2–28 129·8]). Cardiovascular diseases were the second leading cause of NCD burden in 2017, resulting in 22·9 million (21·5–24·3) DALYs (15·1% of the total NCD burden), after the group of disorders categorised as other NCDs (28·8 million [25·1–33·0] DALYs, 19·1%). These categories were followed by neoplasms, mental disorders, and digestive diseases. Although crude DALY rates for all NCDs have decreased slightly across sub-Saharan Africa, age-standardised rates are on the rise in some countries (particularly those in southern sub-Saharan Africa) and for some NCDs (such as diabetes and some cancers, including breast and prostate cancer). Interpretation: NCDs in sub-Saharan Africa are posing an increasing challenge for health systems, which have to date largely focused on tackling infectious diseases and maternal, neonatal, and child deaths. To effectively address these changing needs, countries in sub-Saharan Africa require detailed epidemiological data on NCDs. Funding: Bill & Melinda Gates Foundation, National Health and Medical Research Centre (Australia).